COMPONENTS OF SUCCESS ON THE PATH TO PROLONGATION OF THE BREAST-FEEDING - O. V. Kachalova ("Paediatrician" Publishers LLC, 2013)
Breast milk is a perfect nutrition for infants during their first year of life. Despite the enormous significance of breast feeding for the formation of children health, its prevalence is still very low. Careful doctors' attention to every woman, consulting on the issues of breast feeding will help to overcome its inadequate prevalence and prolong its duration to the maximum. Advantages of the breast feeding, including situations when a child requires supplementary bottle feeding, are described in this article. Selection of appropriate nipples and bottles, for one thing, will help to reduce children's anxiety, associated with colic, and, in the second place, will contribute to maintaining of the breast feeding, if the process of suction from bottles is analogous to the process of feeding from mother's breast.